To Study The Correlation Between Foramen Magnum Index And Cranial Index In Indian Population - Mumal Nagwani*, Geetanjali Srivastava, Archana Rani (Innovative Journal of Medical and Health Sciences, 2020)
Purpose: The cranium base is complex, as well as extremely attractive. The foramen magnum is an important characteristic of cranium base. A transcondylar surgical method requires knowledge of the anatomical features of this region. Foramen magnum index and cranial index were evaluated to establish a correlation, if any, between the dimensions of skull and foramen magnum and an attempt was made to provide a baseline data for better surgical approach in this region so that overall morbidity and mortality could be minimized. Material and Methods: Various diameters of foramen magnum and of cranium were examined to calculate the two index using an electronic digital sliding caliper in 120 adult North Indian dry skulls of unknown age and gender. Results: The mean Foramen Magnum Index (FMI) was 78.715.94. The mean cranial index was found to be 73.827.06.The p-value is >0.05, r = 0.004 (Weak correlation) indicating a weak correlation between two parameters. Conclusion: The results primarily help the anatomists and a medico-legal expert to find out the cranial index from the Foramen Magnum Index through the provision of base line data. Secondly, it provides an important information to clinicians and neurosurgeons to approach the cranial base with maximum safety and minimal mortality and morbidity. Key words: Foramen Magnum–Foramen Magnum Index–Variation–Cranial index.